Corporate purpose in a small post-transitional economy: the case of Slovenia. Issue 1 (1st January 2017) - Stubelj, Igor; Dolenc, Primož; Biloslavo, Roberto; Nahtigal, Matjaž; Laporšek, Suzana
Abstract : Firms are driving forces of economic and social development; therefore it is important to understand what is their primary goal or purpose. The aim of the paper is twofold. First, the paper presents baseline theoretical concepts on the firms' purposes. Secondly, the paper presents the results of the empirical study in Slovenia with which we tried to determine how firms' purposes are perceived by their managers and how they see their responsibility to owners and other stakeholders. The empirical study was based on a survey that was sent to the management of 1400 Slovenian medium-sized and big companies, of which about one third responded. The survey questionnaire was pre-tested through interviewing five top managers in five Slovenian firms with different ownership structure. On the basis of the empirical study it is possible to conclude that, on average, Slovenian firms put the interests of all stakeholders before the interests of only shareholders. So it seems that the majority of managers follow the stakeholder approach in the governance model.